Model and experiences of initiating collaboration with traditional healers in validation of ethnomedicines for HIV/AIDS in Namibia - Chinsembu Kazhila C (BMC, 2009)
Abstract Many people with Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) in Namibia have access to antiretroviral drugs but some still use traditional medicines to treat opportunistic infections and offset side-effects from antiretroviral medication. Namibia has a rich biodiversity of indigenous plants that could contain novel anti-HIV agents. However, such medicinal plants have not been identified and properly documented. Various ethnomedicines used to treat HIV/AIDS opportunistic infections have not been scientifically validated for safety and efficacy. These limitations are mostly attributable to the lack of collaboration between biomedical scientists and traditional healers. This paper presents a five-step contextual model for initiating collaboration with Namibian traditional healers in order that candidate plants that may contain novel anti-HIV agents are identified, and traditional medicines used to treat HIV/AIDS opportunistic infections are subjected to scientific validation. The model includes key structures and processes used to initiate collaboration with traditional healers in Namibia; namely, the National Biosciences Forum, a steering committee with the University of Namibia (UNAM) as the focal point, a study tour to Zambia and South Africa where other collaborative frameworks were examined, commemorations of the African Traditional Medicine Day (ATMD), and consultations with stakeholders in north-eastern Namibia. Experiences from these structures and processes are discussed. All traditional healers in north-eastern Namibia were willing to collaborate with UNAM in order that their traditional medicines could be subjected to scientific validation. The current study provides a framework for future collaboration with traditional healers and the selection of candidate anti-HIV medicinal plants and ethnomedicines for scientific testing in Namibia.